2012
DOI: 10.1109/tmtt.2012.2216283
|View full text |Cite
|
Sign up to set email alerts
|

A Directivity-Enhanced Directional Coupler Using Epsilon Negative Transmission Line

Abstract: In this paper, a high directivity parallel coupled line coupler using the negative (ENG) transmission line is proposed. With the aid of even-and odd-mode analysis, it is shown that by using ENG transmission lines in a parallel coupled line coupler, the even-and odd-mode phase velocities can become equal at a desired frequency. Hence, the directivity of a coupler can be infinite theoretically. The coupler circuit model and closed-form relations for lumped elements of this model are presented. In addition, a des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Alternatively, one of the other widely proposed compensation methods includes connecting lumped components at the ends or center of the coupled lines [15,16]. The discussion of impedance mismatch via additional coupled line and epsilon negative transmission line are presented in [17,18]. It has been shown that high directivity for directional couplers can also be obtained using multilayer configuration [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, one of the other widely proposed compensation methods includes connecting lumped components at the ends or center of the coupled lines [15,16]. The discussion of impedance mismatch via additional coupled line and epsilon negative transmission line are presented in [17,18]. It has been shown that high directivity for directional couplers can also be obtained using multilayer configuration [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The coupled spur line [5], and reflected power canceller approach [6] work within a narrow band. The Epsilon negative transmission line [7] was used but it needs more number of unit cells to improve the accuracy, which leads to fabrication difficulty. Delay lines [8] were used, but the coupler occupies more space than the conventional one.…”
Section: Introductionmentioning
confidence: 99%
“…The coupled spur line [5], and reflected power cancel ler approach [6] work within a narrow band. The epsilon negative transmission line [7] was used, but it needs more number of unit cells to improve the accuracy, which leads to fabrication difficulty. Delay lines [8] were used, but the coupler occupies more space than the conventional one.…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of the coupler are, that the structure is planar, there is no special fabrica tion technique needed, no vias are used, and the con struction is simpler when compared to other methods [7,[9][10][11], and it does not require any iteration design process [3,4].…”
Section: Introductionmentioning
confidence: 99%